The Hong Kong protests will not undermine it as a leading global financial centre. Issue 3 (2nd July 2020) - Meyer, David R.
ABSTRACT: Critics claim the 2019 protests in Hong Kong undermine it as a leading global financial centre. Drawing on the 'geography of finance' research and its focus on financial networks as a means to explain how financial centres operate and other empirical evidence, this article argues that Hong Kong's status as the leading Asia-Pacific financial centre and as head of China's financial centre networks is secure for three reasons. China's government will continue to support it; Hong Kong's financial networks possess extraordinary scale and sophistication; and no viable alternative centre has emerged to challenge Hong Kong as Asia-Pacific leader.